Evolution of cookery - Hassebroek, Mamie Magdelene (My University, 1904)
Introduction: Cookery is the most ancient and the most important of the arts. That one must eat to live is beyond question. As it is through food and drink that man derives the strength for his highest mental activities and physical well-being, the selection and preparation of food should receive the greatest consideration.
Citation: Hassebroek, Mamie Magdelene. Evolution of cookery. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Cooking; History of Cooking; Cooking Techniques; Theses